Effects of herbicide dissolved in ultrafine bubble water on weeding effect in kudzu (Pueraria lobata (Willd.) Ohwi) - Hamada, Kazutoshi; Kondo, Tsukasa (Journal of Weed Science and Technology, 2024)
Kudzu [Pueraria lobata (Willd.) Ohwi] control along highways has involved an integrated approach, including landscape maintenance, environmental preservation, and traffic safety. Given the increasing importance of herbicide use for kudzu control, herbicides must be applied judiciously to minimize their overall usage in the future. In this study, we explored the possibility of enhancing herbicide efficacy and reducing usage by examining the impact of herbicides dissolved in ultrafine bubble (UFB) water on kudzu using a physiological approach. Specifically, the herbicide metsulfuron-methyl (MSM) was dissolved in either tap or UFB water to prepare standard (60 g a.i./ha), half (30 g a.i./ha), and quarter (15 g a.i./ha) doses. These formulations were applied to kudzu foliage. On day 7, leaf browning occurred under tap and UFB water treatments with MSM at 60 g a.i./ha. However, photographic analysis revealed that circumnutation had almost ceased after day 1 with UFB water containing MSM at 60 g a.i./ha, contrasting with 60 g a.i./ha MSM in tap water, where it was delayed by 4 days. On day 12, compared with day 1, chlorophyll fluorescence yield (Fv/Fm) had decreased by 36% and 25% under 60 g a.i./ha MSM treatments in UFB and tap water, respectively. After 24 h of treatment, MSM absorption increased, on average, 1.6-fold in UFB-treated plants. These findings suggest that UFB water enhances MSM absorption in leaves, leading to a rapid reduction in physiological effects.